2017
DOI: 10.3390/nu9121320
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Phytosterols Extracted from Diascorea alata on the Antioxidant Activity, Plasma Lipids, and Hematological Profiles in Taiwanese Menopausal Women

Abstract: The efficacy of phytosterols extracted from Diascorea alata on antioxidant activities, plasma lipids and hematological profiles was assessed in postmenopausal women. Gas chromatography and mass spectrophotometry was employed to determine the steroid content of Taiwanese yam (Diascorea alata cv. Tainung No. 2). A two-center, randomized, double-blind, placebo-controlled clinical investigation on 50 postmenopausal women randomly assigned to two groups treated for 12 months with placebo or two sachets daily of Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 64 publications
3
18
0
Order By: Relevance
“…Phytosterols are known for the decreasing effect against total cholesterol and LDL-cholesterol, important risk factors in cardiovascular diseases [48]. Moreover, the consumption of plant sterols has been shown to increase the antioxidant activity [49]. Our study found quantities of phytosterols in HI which are in line with those in nuts [50] and proved that this by-product can be a source of natural sterols with several health benefits.…”
Section: Resultssupporting
confidence: 74%
“…Phytosterols are known for the decreasing effect against total cholesterol and LDL-cholesterol, important risk factors in cardiovascular diseases [48]. Moreover, the consumption of plant sterols has been shown to increase the antioxidant activity [49]. Our study found quantities of phytosterols in HI which are in line with those in nuts [50] and proved that this by-product can be a source of natural sterols with several health benefits.…”
Section: Resultssupporting
confidence: 74%
“…The duration of trials was between 3 and 52 weeks. Six studies were conducted in women (Hsu, Kuo, & Huang, ; Li & Xing, ; Matvienko et al, ; Plat & Mensink, ; Plat, Van Onselen, Van Heugten, & Mensink, ; Stelmach‐Mardas, Walkowiak, Zagrodzki, Grygiel‐Górniak, & Przysławski, ), five in men (Esther et al, ; Gao, Wang, Wang, & Guo, ; Jones, Ntanios, Raeini‐Sarjaz, & Vanstone, ; Plat et al, ), and the rest of eligible studies involved both genders. Forty‐seven studies had a single‐arm parallel group whereas 32 studies had a crossover design (Abumweis et al, ; de Graaf et al, ; De Smet et al, ; Demonty, Chan, Pelled, & Jones, ; Esther et al, ; Farquhar & Sokolow, ; Fuentes et al, ; Hallikainen et al, ; Hendriks, Weststrate, Van Vliet, & Meijer, ; Ho, Liu, & Loke, ; Jones, Vanstone, Raeini‐Sarjaz, & St‐Onge, ; Kassis, Vanstone, Abumweis, & Jones, ; Naumann, Plat, & Mensink, ; Neil, Meijer, & Roe, ; Ottestad et al, ; Plat et al, ; Plat & Mensink, ; Theuwissen & Mensink, ; Thomsen, Hansen, Christiansen, Green, & Berger, ; Volpe et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐seven studies had a single‐arm parallel group whereas 32 studies had a crossover design (Abumweis et al, ; de Graaf et al, ; De Smet et al, ; Demonty, Chan, Pelled, & Jones, ; Esther et al, ; Farquhar & Sokolow, ; Fuentes et al, ; Hallikainen et al, ; Hendriks, Weststrate, Van Vliet, & Meijer, ; Ho, Liu, & Loke, ; Jones, Vanstone, Raeini‐Sarjaz, & St‐Onge, ; Kassis, Vanstone, Abumweis, & Jones, ; Naumann, Plat, & Mensink, ; Neil, Meijer, & Roe, ; Ottestad et al, ; Plat et al, ; Plat & Mensink, ; Theuwissen & Mensink, ; Thomsen, Hansen, Christiansen, Green, & Berger, ; Volpe et al, ). Included studies were carried out in patient with dyslipidemia (Varady et al, ; Ottestad et al, ; Gylling, Hallikainen, Nissinen, & Miettinen, ; Bañuls et al, ; Hironaka, Shioya, Matsubara, Matsuoka, & Itakura, ; Sukmaniah et al, ; Becker et al, ; Stelmach‐Mardas et al, ; Furuncuoğlu, Başar, Alici, & Şengül, ; Abumweis et al, ; Cabezas, De Vries, Van Oostrom, Iestra, & Van Staveren, ; de Graaf et al, 2002; De Jong et al, ; Demonty et al, ; Fuentes et al, ; Gylling et al, ; Hallikainen, Kurl, Laakso, Miettinen, & Gylling, ; Hallikainen, Sarkkinen, Gylling, Erkkilä, & Uusitupa, ; Hallikainen & Uusitupa, ; Hendriks et al, ; Hsu et al, ; Jones et al, ; Jones et al, ; Kassis et al, ; Korpela et al, ; Lestiani et al, ; Matvienko et al, ; Neil et al, ; Plat & Mensink, ; Plat et al, ; Smet, Mensink, & Plat, ; Solà et al, ; Theuwissen and Mensink, 2007; Thomsen et al, ; Volpe et al, ; Woodgate, Chan, & Conquer, ), diabetes (Gao et al, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The triterpenes and phytosterols are generally found in abundance in the plants and are structurally resemble to the molecule of cholesterol [17]. These compounds are recognized for their hypolipidemic, antioxidant [18] and antiinflammatory effects [19], as well as, have been highlighted by their anticancer potential [20].…”
Section: Introductionmentioning
confidence: 99%